1998
DOI: 10.2807/esm.03.10.00087-en
|View full text |Cite
|
Sign up to set email alerts
|

ESEN : a comparison of vaccination programmes Part one: diphtheria

Abstract: The aim of the European Sero-Epidemiology Network (ESEN) is to coordinate and harmonise the serological surveillance of immunity to vaccine preventable diseases in eight countries in Europe (Denmark, England, France, Germany, Italy, the Netherlands, Finla

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The seroprofile shows very low levels of susceptibility in all age groups over the age of one year (Fig. 2), reflecting the relatively long history of rubella vaccination in Finland with high levels of coverage [14,15]. For the older age groups (more than 35 years), seropositivity largely corresponds to naturally acquired infection from the pre-vaccination era.…”
Section: Finlandmentioning
confidence: 99%
See 1 more Smart Citation
“…The seroprofile shows very low levels of susceptibility in all age groups over the age of one year (Fig. 2), reflecting the relatively long history of rubella vaccination in Finland with high levels of coverage [14,15]. For the older age groups (more than 35 years), seropositivity largely corresponds to naturally acquired infection from the pre-vaccination era.…”
Section: Finlandmentioning
confidence: 99%
“…As part of the project, a questionnaire was completed by each participating country on country-specific information on rubella vaccine programme structure, historical vaccine coverage and reported incidence of rubella infection and cases of CRS (see also [14]).…”
Section: Vaccine Programme Structure and Coveragementioning
confidence: 99%
“…A study in Denmark suggested that long-term protection may be assured by a booster dose of Td vaccine administered 20 years after primary immunization [33]. In 1989-1990, on the basis of serosurveys indicating low antibody levels in persons 140 years of age [29], Finland initiated a mass vaccination campaign targeted at adults.…”
Section: Need For Maintenance Of Immunity Against Diphtheria Among Olmentioning
confidence: 99%
“…Td vaccine is recommended in adults in NIS countries and in Bulgaria (at 25 and 35 years of age) [32]. Several European countries have added extra doses of diphtheria toxoid-containing vaccines in their school-based immunization programs and for travelers [29]. A study in Denmark suggested that long-term protection may be assured by a booster dose of Td vaccine administered 20 years after primary immunization [33].…”
Section: Need For Maintenance Of Immunity Against Diphtheria Among Olmentioning
confidence: 99%
See 1 more Smart Citation